Address microfilm challenges with low‐cost reader/scanner. Issue 3 (May 2016) - Hope, Joan
Abstract : Do you have records from years past stored on microfilm or microfiche? Maybe you've hoped to convert them to an electronic format, but an imaging project is just too expensive. Or maybe you just need an inexpensive machine to view the files on the rare occasions you need them, and you'd prefer it didn't take up too much space in your office.